Magnetic resonance imaging‐guided transurethral ultrasound ablation in patients with localised prostate cancer: 3‐year outcomes of a prospective Phase I study. (1st November 2020) - Nair, Shiva M.; Hatiboglu, Gencay; Relle, James; Hetou, Khalil; Hafron, Jason; Harle, Christopher; Kassam, Zahra; Staruch, Robert; Burtnyk, Mathieu; Bonekamp, David; Schlemmer, Heinz‐Peter; Roethke, Matthias C.; et al.
Abstract : Objectives: To report the 3‐year follow‐up of a Phase I study of magnetic resonance imaging (MRI)‐guided transurethral ultrasound ablation (TULSA) in 30 men with localised prostate cancer. Favourable 12‐month safety and ablation precision were previously described. Patients and Methods: As a mandated safety criterion, TULSA was delivered as near whole‐gland ablation, applying 3‐mm margins sparing 10% of peripheral prostate tissue in 30 men. After 12‐month biopsy and MRI, biannual follow‐up included prostate‐specific antigen (PSA), adverse events (AEs), and functional quality‐of‐life assessment, with repeat systematic biopsy at 3 years. Results: A 3‐year follow‐up was completed by 22 patients. Between 1 and 3 years, there were no new serious or severe AEs. Urinary and bowel function remained stable. Erectile function recovered by 1 year and was stable at 3 years. The PSA level decreased 95% to a median (interquartile range) nadir of 0.33 (0.1–0.4) ng/mL, stable to 0.8 (0.4–1.6) ng/mL at 3 years. Serial biopsies identified clinically significant disease in 10/29 men (34%) and any cancer in 17/29 (59%). By 3 years, seven men had recurrence (four histological, three biochemical) and had undergone salvage therapy without complications (including six prostatectomies). At 3 years, three of 22 men refused biopsy, and two of the 22 (9%) had clinically significant disease (one new, one persistent). Predictors of salvage therapy requirement included less extensive ablation coverage and higher PSA nadir. Conclusion: With 3‐year Phase I follow‐up, TULSA demonstrates safe and precise ablation for men with localised prostate cancer, providing predictable PSA and biopsy outcomes, without affecting functional abilities or precluding salvage therapy.